MENGHADAPI ANCAMAN ALIH FUNGSI LAHAN KEBIJAKAN DESENTRALISASI UNTUK KEBERLANJUTAN SUBAK DI PROVINSI BALI - Angga, I Made Prastika (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
The Indonesian government has enacted Law No. 41/2009 on the Protection of Sustainable Food Agricultural Land as a government decree that aims to protect agricultural land from the problem of land conversion that continues to increase every year. This agricultural land protection policy is the basis for decisions in controlling land conversion. The purpose of this research is to describe and illustrate the decentralization policy for Subak Sustainability in Bali. This research uses a qualitative research method with a literature review approach through online search sources through Google Scholar. The results of this study Decentralization of the subak system is an important step to maintain local wisdom and environmental sustainability in Bali. By giving more authority and resources to local communities, subak can better adapt to modern challenges and remain an important foundation for Bali's social and economic life. Through strong cooperation between the government, local communities, and various stakeholders, subak can continue to thrive as an example of best practice in sustainable natural resource management.Keyword: Decentralization, Subak, Land Conversion